2023
DOI: 10.1039/d2sm00957a
|View full text |Cite
|
Sign up to set email alerts
|

The interplay between chemo-phoretic interactions and crowding in active colloids

Abstract: Many motile microorganisms communicate with each other and their environments via chemical signaling which lead to long-range interactions mediated by self-generated chemical gradients. However, consequences of interplay between crowding and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…While this canonical model of active matter provides a useful foundation for our work, and MIPS-like behavior has been reported in many different bacterial systems [3139], it will not be generally applicable to all bacteria. Additional complexities may arise due to e.g., hydrodynamic, steric, and other mechanical interactions between cells [77– 80], quorum sensing [81, 82], chemotaxis [65, 83, 84], and nutrient-dependent aggregation and proliferation [31, 85]. This study focused on lytic or virulent phages, which infect bacterial cells by injecting genetic material, proliferating inside the cytoplasm, and causing cell lysis to release more phage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this canonical model of active matter provides a useful foundation for our work, and MIPS-like behavior has been reported in many different bacterial systems [3139], it will not be generally applicable to all bacteria. Additional complexities may arise due to e.g., hydrodynamic, steric, and other mechanical interactions between cells [77– 80], quorum sensing [81, 82], chemotaxis [65, 83, 84], and nutrient-dependent aggregation and proliferation [31, 85]. This study focused on lytic or virulent phages, which infect bacterial cells by injecting genetic material, proliferating inside the cytoplasm, and causing cell lysis to release more phage.…”
Section: Discussionmentioning
confidence: 99%
“…While this canonical model of active matter provides a useful foundation for our work, and MIPS-like behavior has been reported in many different bacterial systems [31][32][33][34][35][36][37][38][39], it will not be generally applicable to all bacteria. Additional complexities may arise due to e.g., hydrodynamic, steric, and other mechanical interactions between cells [77][78][79][80], quorum sensing [81,82], chemotaxis [65,83,84], and nutrient-dependent aggregation and proliferation [31,85].…”
mentioning
confidence: 99%
“…Building on this theme, recent research using Brownian dynamics simulations has revealed intriguing behaviors of selfdiffusiophoretic active colloids. 72 These studies show how the interplay of chemical fields with the colloids' movement leads to unique nonequilibrium states, which can induce both attractive forces and repulsive torques. These interactions induce clustering at certain activity levels and densities, and notably, introduce a phase-separation phenomenon known as the chemo-motility-induced phase-separated state.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%
“…Furthermore, the interplay between steric and chemo-phoretic interactions and activity leads to the emergence of a phaseseparated state, very recently coined as the chemo-motilityinduced phase-separated (CMIPS) state. 27 On the other hand, the effect of surface interactions and morphology on motility can be riveting. 28 The motion of a Brownian particle as it flows through periodically modulated potential-energy landscapes in two dimensions experiences a crossover from free-flowing to locked-in transport that depends on the periodicity of the landscape.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the interplay between steric and chemo-phoretic interactions and activity leads to the emergence of a phase-separated state, very recently coined as the chemo-motility-induced phase-separated (CMIPS) state. 27…”
Section: Introductionmentioning
confidence: 99%